Optimization and characterization of halal lipstick formulation containing pitaya (Hylocereous polyrhizhus (weber) britton & rose) seed oil - Kamairudin, Norsuhaili (2015)
Cosmetic is one of the important industries worldwide. Lipstick is one of the decorative cosmetics that have high demand in the market. In this research, pitaya seed oil (PSO) was extracted using two solvents which are n-hexane and ethanol, solvent extraction. Pitaya seed oil (PSO) from both solvents extraction was used in the lipstick formulation with ratio 3:2 (n-hexane: ethanol). Pitaya seed oil was used in this formulation because it has high content of linoleic acid and linolenic acid which are classified as unsaturated fatty acids (UFAs). D-Optimal Mixture Experimental Design was utilized to investigate the influence of the main composition in the lipstick formulation; pitaya seed oil (10-35 % w/w), virgin coconut oil (25-45 % w/w), beeswax (5-25 % w/w), candelilla wax (1-5 % w/w) and carnauba wax (1-5 % w/w) on the physicochemical properties of lipstick. The response Nvariable used is melting point which is one of the important properties of lipstick. Optimization of the five independent variables was carried out to determine an optimum lipstick. The D-Optimal Mixture Experimental Design analysis was showed that the variation in the response (melting point) could be depicted as quadratic model of the main compositions of the formulation. The experimental data fitted sufficiently well into a second-order polynomial model. The predicted melting point gave by Doptimal Mixture Experimental Design (MED) was 45.5 Artificial Neural Network (ANN) was designed as another tools to optimize the ingredients in the lipstick formulation. ANN- Batch Backpropagation give the better prediction of melting point compared to D-optimal MED with the value 45.6 Theptimal ingredients determined by the D-Optimal Mixture Experimental Design and Artificial Neural Network was established to be pitaya seed oil (25% w/w), virgin coconut oil (37% w/w), beeswax (17% w/w), candelilla wax (2% w/w) and carnauba wax (2% w/w). The others ingredients were totaling up to 100% w/w. The actual melting point of the optimized lipstick is 46.0 . Hence, ANN-Batch Backpropagation give better prediction compared to D-optimal Mixture Experimental Design. The other physicochemical properties of the lipstick formulation were also studied. The melting point of the optimized PSO lipstick is 46.0±1.00 with the pH of 6.93±0.01. The texture profiles (hardness, stiffness, brittleness) of the optimized PSO lipstick were (29.759±0.00 g; 5.002±0.01 g/sec; 4.675±0.03 mm, respectively) which are almost like conventional lipstick in the market. From the antioxidant analysis, optimized PSO lipstick showed higher 1,1-diphenyl-2-picryl-hydrazine (DPPH) scavenging activity compared to optimized lipstick without PSO. The optimized PSO lipstick was stable after undergoing stability test at 5 , 27 , 37 and free-thaw cycle for 3 months and the color remained unchanged. The total microbial counts for the optimum PSO lipstick were <1000 cfug-1 and complied with Malaysia Cosmetic Directive microbial limit test. The toxic contaminants had also been studied. Three metals were analyzed which are lead, arsenic and cadmium which is the content of the metals in optimum lipstick are 0.09 ppm, 0.034 ppm and 0.027 ppm, respectively. The halal lipstick containing pitaya seed oil was successfully developed and characterized. It is safe and efficient for human lips care.